2022
DOI: 10.3389/fmicb.2022.1020628
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin increased semen quality of Duroc boars by improving gut microbes and blood metabolites

Abstract: Taxifolin (TAX), as a natural flavonoid, has been widely focused on due to its strong anti-oxidation, anti-inflammation, anti-virus, and even anti-tumor activity. However, the effect of TAX on semen quality was unknown. The purpose of this study was to analyze the beneficial influences of adding feed additive TAX to boar semen in terms of its quality and potential mechanisms. We discovered that TAX increased sperm motility significantly in Duroc boars by the elevation of the protein levels such as ZAG, PKA, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
1
5
0
2
Order By: Relevance
“…Previous studies have shown that flavonoids could improve the quality of Dulocke boar sperm by increasing the relative abundance of intestinal probiotics. 39 Our results found the same changing trend for those probiotics, such as Intestinimonas , Butyrivibrio , and Coprococcus . Probiotics, as mentioned earlier, can promote the cycle of butyrate to synthesize short-chain fatty acids, some of which may promote spermatogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have shown that flavonoids could improve the quality of Dulocke boar sperm by increasing the relative abundance of intestinal probiotics. 39 Our results found the same changing trend for those probiotics, such as Intestinimonas , Butyrivibrio , and Coprococcus . Probiotics, as mentioned earlier, can promote the cycle of butyrate to synthesize short-chain fatty acids, some of which may promote spermatogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Hashem et al found that feeding male rabbits with plant extracts significantly enhanced the sperm quality and antioxidant capacity, mainly through high-density lipoprotein transporting cholesterol to the steroid-producing tissue similar to the testis, and eliminating excess low-density lipoprotein through the liver ( 45 ). Zhou and co-workers demonstrated that adding taxifolin (TAX) to the basal diet could improve boar semen quality by increasing sperm motility and sperm concentration ( 46 ). Another study reported that dietary supplementation of antioxidants, such as lysine and L-arginine, could improve sperm quality in boars ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IHF methods for boar sperm have been reported in our previous articles ( n = 9 per group) ( Zhou et al., 2022 ). Primarily, the boar sperm was fixed in 4% paraformaldehyde for 1 h, then air-dried and spread on the slides covered with poly-L-lysine.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for the analysis of fecal microbiota was reported in our previous study ( Zhou et al., 2022 ) ( n = 9 per group).…”
Section: Methodsmentioning
confidence: 99%